Development of Interactive Teaching Material of Semantic Course Based on Local Wisdom of Brebes - Kurniawan, Prasetyo Yuli; Saputri, Nervi Yani (Pascasarjana Universitas Negeri Semarang, 2018)
Teaching materials in colleges highly support success of students in following their lecture. Moreover, the teaching material need integration of Brebes’ local wisdom in order that the students have understanding on glorious values available to Brebes. The objective of this study is to describe need to develop interactive teaching materials based on local wisdom of Brebes pursuant to perception of students and lecturers, to make draft of interactive teaching materials based on local wisdom of Brebes, and to test effectiveness of interactive teaching materials based on the local wisdom of Brebes. This study was conducted by research and development methods using steps of literature study, from planning of research to implementation of end-product. Testing was conducted on limited scale. The results of study are interactive teaching materials that have met lecturers and students’ needs and principles of teaching material development. Moreover, the interactive teaching materials are effectively applied to students of PBSI UMUS in semantic material.